The Importance of Sharia Business Ethics in Creating a Tolerant and Peaceful Economic Environment - Rizka Nur Aulia; Salsabilah Ilmar Fandini; Rifqiyati Nur Fauzi; Rizal Maulana (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
This study explores the importance of implementing Sharia business ethics in creating a tolerant and peaceful economic environment, especially in the context of a multicultural global society. Sharia business ethics offers universal principles such as justice, transparency, and fair conflict resolution, which focus not only on achieving economic profit but also on promoting social harmony and common welfare. By emphasizing the values of tolerance and diversity, which are integral parts of Islamic teachings, this study shows that implementing Sharia principles can have a significant positive impact on economic development. This implementation, if supported by education, training, and strengthening individual capacity, has the potential to create a stable, trustworthy, and inclusive business environment. In addition, Sharia business ethics can serve as a comprehensive guide in building a just, harmonious, and tolerant society. Thus, this study confirms that Sharia business ethics is not just a set of rules, but a comprehensive approach to achieving economic and social justice in a global society.